New fossil records of Xyelidae (Hymenoptera) from the Middle Jurassic of Inner Mongolia, China – Corrigendum - Zheng, Yan; Hu, Haiyan; Chen, Dong; Chen, Jun; Zhang, Haichun; Rasnitsyn, Alexandr P. (European Journal of Taxonomy, 2023)
The present corrigendum corrects errors that occurred in: Zheng Y., Hu H., Chen D., Chen J., Zhang H. & Rasnitsyn A.P. 2021. New fossil records of Xyelidae (Hymenoptera) from the Middle Jurassic of Inner Mongolia, China. European Journal of Taxonomy 733: 146–159. https://doi.org/10.5852/ejt.2021.733.1229